Los setenta años de la OEA - Arrighi, Jean-Michel (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
In 2018, the OAS celebrates seventy years of its creation. After a brief presentation on the evolution of its founding Charter of 1948 and of the Inter-American System from its inception at the end of the 19th century until the entry of the last members of the OAS in 1991, this article gives a succinct account of the successes achieved by the Organization throughout its existence, highlighting the achievement of relative peace among its member states provided by the construction of an Inter-American normative and institutional fabric based on the fundamental principles of legal equality of States, non-intervention, respect for international law and peaceful settlement of disputes. Subsequently, the article reviews the evolution of these principles during the seventy years of the Organization and the notable progress made, primarily in the development of a regional system for the protection of human rights and for the defense of representative democracy in the Hemisphere. Finally, the article highlights other more recent legal developments in the field of private international law, access to information, combating corruption, organizedcrime and drug trafficking, as well as legal and judicial cooperation.In the end, the article provides a review of the results achieved by the OAS vis-à-vis the emergence of new subregional organizations. These new organizations have not managed to replace the OAS as the political space of legal elaboration, defense of rights human rights and democracy, unique in the region, which encompasses all of its member states on an equal footing.

En 2018, la OEA celebra los setenta años de su creación. Luego de una breve presentación sobre la evolución de su Carta fundacional de 1948 y del sistema interamericano desde sus inicios a fines del siglo XIX hasta el ingreso de los últimos miembros de la OEA en 1991, el presente artículo hace un recuento sucinto de los éxitos alcanzados por la Organización a lo largo de su existencia, destacándose el logro de una relativa paz entre sus Estados miembros proporcionada por la construcción de un tejido normativo e institucional interamericano basado en los principios fundamentales de igualdad jurídica de los Estados, no intervención, respeto al derecho internacional y solución pacífica de las controversias. Posteriormente, se analizan la evolución de dichos principios en el transcurso de los setenta años de la Organización y los notables progresos obtenidos, principalmente en el desarrollo de un sistema regional de protección de los derechos humanos y para la defensa de la democracia representativa en el hemisferio. Finalmente, se destacan otros desarrollos jurídicos más recientes en el ámbito del derecho internacional privado, del acceso a la información, del combate a la corrupción, al crimen organizado y al tráfico de drogas, así como en materia de cooperación jurídica y judicial. Al final se realiza un balance de los resultados conseguidos por la OEA vis-à-vis el surgimiento de nuevos organismos subregionales, los cuáles no han logrado sustituirla como el espacio político, único en la región, de elaboración jurídica, de defensa de los derechos humanos y de la democracia, que abarca a todos sus países en un pie de igualdad.
The OAS at Seventy Years
Keywords: Organización de los Estados Americanos (OEA); Organismos internacionales; Organizaciones regionales; Sistema interamericano; Derecho interamericano; Panamericanismo; Derechos humanos; Democracia; https://purl.org/pe-repo/ocde/ford#5.09.01